The Factors of Zakat Assistance Towards Strengthening Religiosity of Muallaf: Case Study in Terengganu, Malaysia - Jalil, Mohammad Syukri; Awang, Azarudin Bin (CENTRAL ASIA AND THE CAUCASUS, 2022)
The factors of straightening the religiosity of Muslim converts (muallaf) are an important element especially involving zakat assistance. This is due to the fact that the zakat assistance is still an important allocation to muallaf. Thus, there are among muallaf who do not understand the faith of Islam well. As a result, they feel marginalized after embracing Islam. The objective of this article is to identify the factors strengthening influence of the level of religiosity among muallaf through zakat influencing factors which perception, psychology, motivation, environment, and faith. Thus, the design of this work is in the form of inferential statistics using the questionnaire form as the data collection method by structural equation modeling (SEM). There are 136 questionnaire forms analyzed involving the muallaf in Terengganu, Malaysia. Data analysis uses SPSS 22 and the Smart-PLS version 3.2.7. The finding will support continuous development with the aid of muallaf to strengthen religiosity through zakat assistance. There are four factors influencing the straightening religiosity among muallaf that are psychology, perception, motivation, and environment. It is hoped that the success of zakat assistances toward muallaf will produce quality for religion and avoid the negative perception of the public among muallaf.